Pengembangan Logo Usaha untuk Usaha Mikro Kecil Menengah Demi Meningkatkan Citra Usaha di Desa Bumi Nabung Selatan - Muhammad Iqbal; Rizka Reza Tri Agusti; Safira Aulia Nasifa; Septiana Nurjanah; Septiha Andara Putri; Sevy Rachmawati; Siti Marlinah; Cindy Sihaloho; Budi Ariyanto (Jurnal Pengabdian Masyarakat, 2026)
Developing a visual identity through a logo is a crucial strategy for enhancing the image and competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in the digital era. This study aims to describe the process of assisting MSMEs in South Bumi Nabung Village in logo creation to optimize local economic potential, particularly for cassava and processed food products. The method used was a qualitative field study approach, encompassing in-depth interviews, production observations, and direct assistance in logo design using the Canva application. The mentoring focused on two culinary businesses: Ibu Parmi's banana chips business, established in 1991, and Ibu Windi's tempeh chips business, which only started in 2025. Results showed that prior to the intervention, both partners lacked a visual identity due to limited access to technology and understanding of the importance of branding. Through this program, professional logos that represent the product's value have been developed and implemented on packaging to build consumer trust. However, challenges such as traditional production tools, low digital marketing literacy, and damaged road infrastructure continue to hinder distribution. In conclusion, revitalizing visual identity through professional logos is a strategic investment for enhancing the presence of MSMEs in the global digital market.